Answer:
![\large \boxed{\sf \ \ \ p=-11 \ \ \ }](https://img.qammunity.org/2021/formulas/mathematics/high-school/smkacjh7pi7bpuhvpeaqcw0wuguqankk2e.png)
Explanation:
Hello,
![\alpha \text{ and } \beta \text{ are the roots of the following equation}](https://img.qammunity.org/2021/formulas/mathematics/high-school/s16h6vv05u8h51fnjtvivf5xle2vmyrbnb.png)
![2x^2+6x-7=p](https://img.qammunity.org/2021/formulas/mathematics/high-school/o0geclzw0yvfiuwuha6q8v2csotjcblg0k.png)
It means that
![2\alpha^2+6\alpha-7=p \\\\2\beta ^2+6\beta -7=p \\\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/ccnynva4l4eeksiommfvkhoedbvo4oo3j8.png)
And we know that
![\alpha= 2\cdot \beta](https://img.qammunity.org/2021/formulas/mathematics/high-school/gkjqk0dfautrn5opa94cnwri3snb4eiakd.png)
So we got two equations
![2(2\beta)^2+6\cdot 2 \cdot \beta -7=p \\\\<=>8\beta^2+12\beta -7=p\\\\ and \ 2\beta ^2+6\beta -7=p \ So \\\\\\8\beta^2+12\beta -7 = 2\beta ^2+6\beta -7\\\\<=>6\beta^2+6\beta =0\\\\<=>\beta(\beta+1)=0\\\\<=> \beta =0 \ or \ \beta=-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/l20ak3xyuvzxefez43nepqabsu16inwxay.png)
For
![\beta =0, \ \ \alpha =0, \ \ p = -7](https://img.qammunity.org/2021/formulas/mathematics/high-school/hdt1rqyc1dq4jvhado9xi2zrdtk0llj870.png)
For
![\beta =-1, \ \ \alpha =-2, \ \ p= 2-6-7=-11, \ p=2*4-12-7=-11](https://img.qammunity.org/2021/formulas/mathematics/high-school/yntcghks0rm0rajvmbd2uniwgwuew3949l.png)
I assume that we are after two different roots so the solution for p is p=-11
b)
![\alpha +2 =-2+2=0 \ and \ \beta+2=-1+2=1](https://img.qammunity.org/2021/formulas/mathematics/high-school/t7lozbefoayvnmeh6jw65tp722afch1v5t.png)
So a quadratic equation with the expected roots is
![x(x-1)=x^2-x](https://img.qammunity.org/2021/formulas/mathematics/high-school/pdv5dtwtih83dcqyq3cznhozbp7h1so474.png)
Hope this helps.
Do not hesitate if you need further explanation.
Thank you